2016
DOI: 10.1039/c6sm00966b
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal particle adsorption at liquid interfaces: capillary driven dynamics and thermally activated kinetics

Abstract: The adsorption of single colloidal microparticles (0.5-1 µm radius) at a water-oil interface has been recently studied experimentally using digital holographic microscopy [Kaz et al., Nat. Mater., 2012, 11, 138-142]. An initially fast adsorption dynamics driven by capillary forces is followed by an unexpectedly slow relaxation to equilibrium that is logarithmic in time and can span hours or days. The slow relaxation kinetics has been attributed to the presence of surface "defects" with nanoscale dimensions (1-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 45 publications
2
43
1
Order By: Relevance
“…For example, single microparticles adsorbed at liquid-liquid interfaces have exhibited crossovers from initially fast dynamics, driven by capillary forces, to a much slower "kinetic" relaxation that can be nearly logarithmic in time, as first discovered by Kaz et al 5 and subsequently studied by other groups. [6][7][8][9][10] Similar near-equilibrium behavior has been also observed in the imbibition/drainage of water/oil in microscale capillaries with nanoscale surface roughness. 11 The observed near-equilibrium phenomena, resembling physical ageing in dense colloidal systems that exhibit jamming transitions, [12][13][14][15] have been attributed to random thermally activated transitions between multiple metastable states induced by numerous nanoscale "defects" on the solid surface.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…For example, single microparticles adsorbed at liquid-liquid interfaces have exhibited crossovers from initially fast dynamics, driven by capillary forces, to a much slower "kinetic" relaxation that can be nearly logarithmic in time, as first discovered by Kaz et al 5 and subsequently studied by other groups. [6][7][8][9][10] Similar near-equilibrium behavior has been also observed in the imbibition/drainage of water/oil in microscale capillaries with nanoscale surface roughness. 11 The observed near-equilibrium phenomena, resembling physical ageing in dense colloidal systems that exhibit jamming transitions, [12][13][14][15] have been attributed to random thermally activated transitions between multiple metastable states induced by numerous nanoscale "defects" on the solid surface.…”
supporting
confidence: 65%
“…Although the dynamics of spontaneous droplet spreading has been extensively investigated, [16][17][18][19][20][21][22][23][24][25] to the best of our knowledge no previous study has reported a crossover from capillary driven dynamics and power-law spreading to slow logarithmic relaxation and physical ageing behavior and a) carlos.colosqui@stonybrook.edu analogous to that observed for the adsorption of single colloidal particles. [5][6][7]10 Spreading studies have established that the droplet contact radius R in different dynamic regimes follows a power law R(t) ∝ t α with exponents α varying from 0.1 to 1. Spreading regimes where R(t) ∝ t 0.5 have been observed at short initial times where inertial effects are significant, for droplets of liquids with low viscosity ( 10 mPa·s) immersed in a gas/vapor phase.…”
mentioning
confidence: 99%
“…37 In fact, it has been previously shown that the presence of the double layer provides an electrostatic barrier and can retard or prevent the adsorption of particles at soft interfaces. 38,39 The intensity of this barrier can be surprisingly higher than the hydrodynamic forces pushing the particle towards the droplet. 40,41 As a result of that, even in the presence of weak forces, external work must be often applied via high shear or sonication in order to observe adsorption of particles at a reasonable rate, which would confirm our results.…”
Section: On the Adsorption Of The Pickering Stabilizer Onto Monomer Dmentioning
confidence: 99%
“…We note that these models capture only the gross features of the trajectories. A more recent model [26] …”
Section: Introductionmentioning
confidence: 99%